Degradation of Methyl Parathion by a Soil Bacterial Isolate: A Pot study - Mishra, Archana; Khan, Jamaluddin; Pandey, A. K. (Journal of Experimental Sciences)
The indiscriminate use of chemicals fertilizers and pesticides have not only deteriorated the environment but also the groundwater resources as well .Their intensive consumption causes deleterious effects on plant, animal and aquatic ecosystems thereby causing serious problems related to health. Since these are one of the factors which are responsible for the contamination of air, water and terrestrial ecosystems and also the cause of disruption of biogeochemical cycling, it is extremely important to bring down ,the toxicity levels that these chemicals impose on the environment, by the use of effective technology, which is cost effective and safe. It has been suggested that biodegradation becomes an attractive option for destruction of pesticides since it utilizes a natural process and offers the potential for being cost effective as well as safe technology Thus the present study deals with the isolation and use indigenous bacteria for degradation of an organophosphorous pesticide- methyl parathion present in the soil samples which were collected from the pesticide contaminated agricultural field.